Early detection of intractable postpartum hemorrhage - Saori Yoshimura; Yutaka Iwagoi; Fumitaka Saito; Chisato Kodera; Rumi Sasaki; Munekage Yamaguchi; Takashi Ohba; Eiji Kondoh (Scientific Reports)
Abstract Postpartum hemorrhage (PPH) is a leading cause of maternal mortality worldwide, with timely detection complicated by the inability to visualize bleeding within the uterine cavity. This study aimed to develop a method for early detection of intractable PPH, characterized by arterial contrast extravasation on dynamic CT (PRACE), often requiring uterine arterial embolization. The study comprised two components: (1) an ex vivo study, evaluating the PRACE visualization model using a postpartum uterine cavity simulation, and (2) an in vivo study assessing whether the time interval for bleeding to appear at the vagina (TI-V) could serve as an indicator of intractable PPH. The ex vivo simulation of PPH at various flow rates suggested that the overflow time from the uterine cavity may assist in stratifying life-threatening PPH. In the in vivo study, TI-V was measured in cases of uncomplicated vaginal delivery and severe PPH, including those transported for treatment. The results indicated that a TI-V of less than 2 s strongly predicted intractable PPH, with a positive predictive value of 100% and a negative predictive value of 98.2%. This straightforward method could significantly improve maternal health outcomes by enabling early identification and management of severe PPH.